Endoscopic Management of Malleus Head Fixation in Revision Stapes Surgery. Issue 5 (June 2020) - Fernandez, Ignacio Javier; Botti, Cecilia; Fermi, Matteo; Presutti, Livio
Abstract : Objective: Malleus ankylosis is an uncommon finding during stapes surgery, which can result in functional failure if undetected during primary surgery. Its management can be difficult and different approaches and solutions have been described to date, most of which require interruption of the ossicular chain. We report the management of such condition through a transcanal endoscopic technique, with preservation of ossicular chain integrity. Patients: The procedure was carried out in a patient affected by otosclerosis with persistent hearing loss after primary stapes surgery. Intervention: Surgical treatment of malleus head fixation through a totally endoscopic transcanal approach during revision stapes surgery. Main Outcome Measure: Pure tone audiometry, speech audiometry. Results: The patient experienced a complete closure of the air-bone gap. No postoperative vertigo or sensorineural hearing loss were observed. Conclusions: The present report describes the transcanal endoscopic management of malleus ankylosis during revision stapes surgery, which has not been previously reported in the literature. Pearls related to this approach and advantages in comparison to previously described approaches of the literature are discussed as well.